Ocean-crossing wayfarer : to Iceland and Norway in an open boat - Dye, Frank; Dye, Margaret (Newton : David & Charles, 1977)
The sailing exploits of Frank Dye and his wife Margaret are already known to thousands in many parts of the world.
Part I. Iceland -- Interlude -- Part III. Interlude.
Keywords: WAYFARER